Genomic insights of a native bacterial consortium for wheat production sustainability - Ayala Zepeda, Marisol; Valenzuela Ruiz, Valeria; Parra Cota, Fannie Isela; Chinchilla-Soto, Cristina; de la Cruz Torres, Eulogio; Ibba, Marí Itria; Estrada-Alvarado, María Isabel; de los Santos Villalobos, Sergio (Elsevier, 2024)
The use of plant growth-promoting bacteria as bioinoculants is a powerful tool to increase crop yield and quality and to improve nitrogen use efficiency (NUE) from fertilizers in plants. This study aimed to bioprospecting a native bacterial consortium ( Bacillus cabrialesii subsp. cabrialesii TE3 T , Priestia megaterium TRQ8, and Bacillus paralicheniformis TRQ65), through bioinformatic analysis, and to quantify the impact of its inoculation on NUE (measured through 15 N-isotopic techniques), grain yield, and grain quality of durum wheat variety CIRNO C2008 grown under three doses of urea (0, 120, and 240 kg N ha -1 ) during two consecutive agricultural cycles in the Yaqui Valley, Mexico. The inoculation of the bacterial consortium (BC) to the wheat crop, at a total N concentration of 123 -225 kg N ha -1 increased crop productivity and maintained grain quality, resulting in a yield increase of 1.1 ton ha -1 (6.0 vs. 7.1 ton ha -1 , 0 kg N ha -1 added, 123 kg N ha -1 in the soil) and of 2.0 ton ha -1 (5.9 vs. 7.9 ton ha -1 , 120 kg N ha -1 added, 104 kg N ha -1 in the soil) compared to the uninoculated controls at the same doses of N. The genomic bioinformatic analysis of the studied strains showed a great number of biofertilization-related genes regarding N and Fe acquisition, P assimilation, CO 2 fixation, Fe, P, and K solubilization, with important roles in agroecosystems, as well as genes related to the production of siderophores and stress response. A positive effect of the BC on NUE at the studied initial N content (123 and 104 kg N ha -1 ) was not observed. Nevertheless, increases of 14 % and 12.5 % on NUE (whole plant) were observed when 120 kg N ha -1 was applied compared to when wheat was fully fertilized (240 kg N ha -1 ). This work represents a link between bioinformatic approaches of a native bacterial inoculant and the quantification of its impact on durum wheat.